Complexo de Ru(II)-perileno diimida para ativação do oxigênio singleto: agente teranóstico em melanoma - Campos, Isabele Aparecida Soares de (Universidade Federal de São Carlos, 2023)
In this study, a new perylene diimide ligand functionalized at the 1,7-bay positions with two pyrrolidine molecules and at the imide positions with 5,10-amino-phenanthroline (PDI-Py) and a new electron donor-acceptor dyad [Ru(phen)2(PDI-Py)]2+ (RuPDI-Py), where phen = 1,10-phenanthroline, was developed for potential applications in photomedicine by combining absorption and emission in the near-infrared region with the ability to generate singlet oxygen (1O2). The electrochemical, photophysical, and photochemical properties of the PDI-Py ligand and the RuPDI-Py dyad were investigated using steady-state and time-resolved spectroscopic techniques in organic solvents and water. The pyrrolidine substituent induced a shift in the absorption (720 nm) and fluorescence (767 nm, EM = 1.75 ns) to the near-infrared region of the PDI-Py ligand. In DMSO, the RuPDI-Py dyad preserved the absorption and fluorescence of the PDI-Py chromophore in the near-infrared region, whereas in the region between 350-550 nm there was an overlap of the absorption bands related to the 1*MLCT and S0→S2 electronic transitions of the chromophores [Ru(phen)3]2+ and PDI-Py, respectively, and the phosphorescence 3*MLCT was completely quenched. Transient absorption studies demonstrated that the excitation of the {Ru(phen)3} moiety in the dyad resulted in rapid photoinduced electron transfer (60 ps) between the constituent chromophores, generating the charge-separated intermediate {Ru3+-(PDI-Py●-) (4 μs) that decays to generate the long-lived triplet state 3*PDI-Py (36 μs), which can sensitize the formation of 1O2 (Δ = 0.40). In water, the RuPDI-Py dyad self-assembled into J-type molecular aggregates, which exhibited 1*PDI-Py fluorescence at 840 nm (τEM = 1.55 ns) and 3*MLCT phosphorescence at 620 nm (τEM = 1.3 μs). Furthermore, excitation of the {Ru(phen)3} moiety resulted in the formation of 3*PDI-Py (15 μs) and the generation of 1O2. The dependence of the photophysical properties of the RuPDI-Py dyad on the wavelength of the excitation light allowed modulation of its biological applications. Using 450 nm visible light, the dyad generated the cytotoxic species 1O2, which induced 100% inhibition of E. Coli colony growth at dyad concentrations above 2.5 μM after light treatment. In vitro studies with human melanoma cells of the MDA-MB-435 cell line demonstrated the photocytotoxicity of the dyad with an IC50 of 2.30 μM (PI > 108), indicating its potential application as a photosensitizer for antimicrobial and antitumor photodynamic therapy. In contrast, using light above 650 nm, only the fluorescence of the dyad in the near-infrared region was observed, which allowed monitoring of its cellular location preferentially in the cytoplasm of MDA-MB-435 cells, as well as monitoring the photoinduced damage by treatment with 450 nm light in cells and in mimetic models of phospholipid membranes, demonstrating the potential application of the dyad as a luminescent biomarker. Finally, polymeric polyacrylonitrile (PAN) nanofibers functionalized with the RuPDI-Py dyad were prepared using the electrospinning method and presented ideal characteristics to act as promising photoactive materials capable of generating 1O2 under irradiation with visible light for future applications in wound healing in the topical treatment of melanoma skin cancer.
Ru(II)-perylene diimide complex for singlet oxygen activation: theranostic agent for melanoma
Keywords: Perileno diimida; Complexos de Rutênio (II); Transferência de elétrons fotoinduzida; Oxigênio singleto; Terapia fotodinâmica; Melanoma; Nanofibras poliméricas; Eletrofiação; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::FOTO-QUIMICA INORGANICA